2018
DOI: 10.1039/c8ra00787j
|View full text |Cite
|
Sign up to set email alerts
|

A highly active worm-like PtMo nanowire for the selective synthesis of dibenzylamines

Abstract: An efficient synthetic pathway of dibenzylamine (DBA) motifs from reductive amination of either aldehydes or nitriles catalyzed by highly active worm-like PtMo nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It is notable that these newly developed PdPt (50 : 50) random alloy nanoparticles had higher catalytic activity for the hydrogenation of aromatic and heterocyclic nitriles to the corresponding secondary amines than any previously reported catalysts (Table S5†). 17–23,27–29…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is notable that these newly developed PdPt (50 : 50) random alloy nanoparticles had higher catalytic activity for the hydrogenation of aromatic and heterocyclic nitriles to the corresponding secondary amines than any previously reported catalysts (Table S5†). 17–23,27–29…”
Section: Resultsmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2022 heterocyclic nitriles to the corresponding secondary amines than any previously reported catalysts (Table S5 †). [17][18][19][20][21][22][23][27][28][29]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other results, they reported that in the reaction of PhCHO and aqueous NH 3 performed in toluene as a solvent at 100°C using 1 bar of H 2 and 0.5 mol-% of PtMo nanowires 83 % yield of Bn 3 N was achieved. [188] EurJOC European Journal of Organic Chemistry Scheme 72. Me3N synthesis from NH 3 and NH 4 Cl.…”
Section: Scheme 63 Synthesis Of Oxyquinoline Tripodal Ligandmentioning
confidence: 99%